The impact of mycobacteria-induced trained immunity on SARS-CoV-2 vaccine responses - Sánchez-Morales, Lidia; Porras, Néstor; Pérez-Domingo, Andrea; Pérez-Sancho, Marta; García-Seco, Teresa; Diaz-Frutos, Marta; Buendia, Aranzazu; Moreno, Inmaculada; Zamora, Leydis; Balseiro, Ana; Risalde, M. A.; Rodriguez-Bertos, Antonio; et al. (Frontiers in Immunology, 2025)
IntroductionBeyond the role of Bacillus Calmette-Guérin (BCG) for tuberculosis prevention, BCG has demonstrated heterologous protective effects. The global health crisis caused by the SARS-CoV-2 virus led to research on whether BCG-induced trained immunity could strengthen antiviral defenses. However, studies reported quite different results on its effect against COVID-19.Methods and resultsIn this study, we evaluated the impact of pre-existing trained immunity induced by a BCG-derived Mycobacterium bovis strain (dpB), in both live and inactivated forms, in combination with SARS-CoV-2 vaccination prior to challenge in a mouse model. While the SARS-CoV-2 vaccine was enough for protection in morbidity and mortality terms, its combination with live dpB significantly enhanced immune responses reflected in higher levels of pro-inflammatory cytokines, reduced pulmonary viral loads, and improved histopathological outcomes. Additionally, the formation of inducible bronchus-associated lymphoid tissue (iBALT) in lungs in vaccinated animals pre-exposed to live dpB points to a potential mechanism for long-term immune surveillance in the respiratory tract.ConclusionsThese immunological findings highlight the potential benefits of integrating trained immunity inducers with pathogen-specific vaccines to enhance immune responses and protection. Further research is needed to optimize immunomodulation strategies, dosing regimens and administration routes to maximize these synergistic effects and prevent potential negative effects.